Ergonomic Risk Assessment of Fabric Measuring and Cutting Workstations: Penilaian Risiko Ergonomis pada Stasiun Kerja Pengukuran dan Pemotongan Kain - Iswahyudi; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Work-related musculoskeletal disorders are often caused by non-ergonomic working postures in manual activities. Specific Background Fabric measuring and cutting processes are commonly performed in awkward positions such as bending and squatting, increasing ergonomic risk. Knowledge Gap However, limited studies evaluate these activities using combined RULA and NERPA assessment methods. Aims This study aims to analyze the working posture of operators in fabric measuring and cutting processes using RULA and NERPA methods. Results The findings show that the measuring activity obtains a RULA score of 6, indicating moderate risk, while the cutting activity reaches a score of 7, indicating high risk requiring immediate action. Using NERPA, both activities show a score of 6, indicating moderate risk requiring improvement. Novelty This study applies dual ergonomic assessment methods to identify risk levels in specific textile work activities. Implications The results support the need for ergonomic workstation design, including the proposed worktable, to reduce posture-related risks and improve worker safety. Keywords: Ergonomic Assessment, RULA Method, NERPA Method, Musculoskeletal Disorders, Work Posture Key Findings Highlights Cutting task shows highest risk classification Both techniques indicate need for corrective action Workstation redesign recommended to reduce strain